2022
DOI: 10.26565/2313-6693-2022-44-01
|View full text |Cite
|
Sign up to set email alerts
|

Quantum, molecular and continuum modeling in nonlinear mechanics of viruses

Abstract: Introdution. Viruses are a large group of pathogens that have been identified to infect animals, plants, bacteria and even other viruses. The 2019 novel coronavirus SARS-CoV-2 remains a constant threat to the human population. Viruses are biological objects with nanometric dimensions (typically from a few tens to several hundreds of nanometers). They are considered as the biomolecular substances composed of genetic materials (RNA or DNA), protecting capsid proteins and sometimes also of envelopes. Objective. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 199 publications
(292 reference statements)
0
1
0
Order By: Relevance
“…A virus capsid is an assembly of proteins that shields viral genomes, possessing remarkable mechanical properties that have captured scientific interest. This fascination has led to extensive studies of various capsids to unveil their elastic behavior [32][33][34]. Computer simulations of nanoindentation experiments [35][36][37][38] have revealed that virus capsids, especially those protecting single-stranded RNA, exhibit significant elasticity.…”
Section: Interior Of Viral Capsidmentioning
confidence: 99%
“…A virus capsid is an assembly of proteins that shields viral genomes, possessing remarkable mechanical properties that have captured scientific interest. This fascination has led to extensive studies of various capsids to unveil their elastic behavior [32][33][34]. Computer simulations of nanoindentation experiments [35][36][37][38] have revealed that virus capsids, especially those protecting single-stranded RNA, exhibit significant elasticity.…”
Section: Interior Of Viral Capsidmentioning
confidence: 99%